1991
DOI: 10.1111/j.1467-8624.1991.tb01571.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aggression in Peer Relations: An Analysis of Aggression Episodes in Boys' Play Groups

Abstract: Although aggression is frequently cited as a major cause of peer social rejection, no more than half of all aggressive children are rejected. Aggressive episode data from experimental play groups of 7- and 9-year-old black males were coded to examine whether qualitative aspects of aggressive behavior, as well as frequency of aggression, determine the relation between aggressiveness and peer rejection. Reactive aggression and bullying were related to peer status among 9-year-olds, but not 7-year-olds, whereas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
162
1
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 180 publications
(175 citation statements)
references
References 34 publications
4
162
1
8
Order By: Relevance
“…The definition implies that by its nature, bullying is proactive rather than reactive aggression. In fact, Coie et al [1991] have further distinguished between two types of proactive aggression, instrumental aggression and bullying, the former referring to behavior in which aggression is used as a means to get an external reward, such as when a child pushes another to take a toy from him/her, the latter to person-directed, "mean" aggression in which no such goal is necessarily detected.…”
Section: Bullies Victims and Bully-victimsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition implies that by its nature, bullying is proactive rather than reactive aggression. In fact, Coie et al [1991] have further distinguished between two types of proactive aggression, instrumental aggression and bullying, the former referring to behavior in which aggression is used as a means to get an external reward, such as when a child pushes another to take a toy from him/her, the latter to person-directed, "mean" aggression in which no such goal is necessarily detected.…”
Section: Bullies Victims and Bully-victimsmentioning
confidence: 99%
“…On the contrary, counteraggressive responses (such as trying to pay back the bully in his own coin, attacking the bully) in bullying situations were rather typical, especially among boy victims. Also, Coie et al [1991], making direct observations of the victims' behavior in play groups, found that when attacked, "escalating" was a rather typical response. Furthermore, there are studies that indicate that victimization is related to reactive aggression [Pellegrini et al, 1999;Poulin and Boivin, 2000b;Schwartz et al, 1998], which also suggests that submissive behavior is not the only response on the part of the victims-they may respond with aggression as well.…”
Section: Bullies Victims and Bully-victimsmentioning
confidence: 99%
“…For example, although average and rejected boys become equally angered and aggressive when provoked, rejected boys respond more aggressively without justification [Coie et al, 1990]. Furthermore, once aggression has started, children who are generally rejected by their peers are more inclined to intensify their aggression and less likely to submit than nonrejected children [Coie et al, 1991]. Of course, cross-sectional designs do not allow us to determine whether rejection leads to aggression, or behaving aggressively increases the likelihood of being rejected.…”
mentioning
confidence: 99%
“…In the phase of stimulus interpretation, aggressive children are less able to recognize the specific intentions and motivations of their interaction partners (e.g., Dodge, Price, Bachorowski, & Newman, 1990). For example, they exhibit a tendency to attribute hostile intentions to them (e.g., Coie, Dodge, Terry, & Wright, 1991;Zelli, Dodge, Lochman, Laird, & Conduct Problems Prevention Research Group, 1999). In the phase of goal clarifying, more egocentric and antisocial goals have been found in aggressive youngsters.…”
Section: Basic Research Backgroundmentioning
confidence: 99%
“…In the phase of goal clarifying, more egocentric and antisocial goals have been found in aggressive youngsters. For example, they try more frequently to maximize to their own utility, even when this harms others, or they are more interested in dominating than maintaining a relationship (e.g., Coie et al, 1991;Crick & Ladd, 1990;Lochman, Wayland, & White, 1993;. In the fourth phase, response access or construction, aggressive children retrieve and generate more aggressive and hostile alternatives Rubin, Bream, & Rose-Krasnor, 1991;Zelli et al, 1999).…”
Section: Basic Research Backgroundmentioning
confidence: 99%